ANALYSIS OF RENAL FUNCTION AFTER ON AND OFF PUMP CORONARY ARTERY BYPASS GRAFTING - João Roberto Breda; Ariadne Pires; Charles Benjamin Neff; Leandro Luongo de Mattos; Luiz Carlos de Abreu; Vitor E. Valenti; Vivian F. Ribeiro; Adriano L. Roque; Jose-Luiz Figueiredo; Rodrigo Daminello Raimundo; Celso Ferreira (Российский кардиологический журнал)
Cardiopulmonary bypass (CPB) is often associated with renal dysfunction, as measured by plasma creatinine levels and hemodialysis rates.Aim. To compare creatinine clearance (CrCl), estimated with the Cockroft and Gault formula, between patients undergoing off-pump coronary artery bypass grafting (OPCAB) versus on-pump CABG (on-CAB).Material and methods. Between April 2008 and April 2009, 119 patients underwent coronary bypass graft surgery. Fifty-eight (58) of these patients underwent OPCAB while 61 had on-CAB. Creatinine clearance, plasma creatinine levels, and clinical outcome were compared between the groups. A creatinine clearance value of 50 mL/minute was accepted as the lowest limit of normal renal function.Results. There were two hospital deaths caused by sepses after pulmonary infection. Creatinine clearance (Preoperative OPCAB 73,64±33,72 x on-CAB 75,70±34,30mL/min; discharge OPCAB 75,73±35,07 x on-CAB 79,07±34,71 mL/ min; p=0,609), and creatinine levels (Preoperative OPCAB 1,04±0,38 x on-CAB 1,13±0,53 mg/dL; discharge OPCAB 1,12±0,79 x on-CAB 1,04±0,29mg/dL; p=0,407) did not show statistically inter-group differences.Conclusion. Deterioration in renal function is associated with higher rates of postoperative complications. No significant difference in CrCl could be demonstrated between the groups.